Rhamnolipids, Microbial Virulence Factors, in Alzheimer's Disease. - Andreadou, Eleni; Pantazaki, Anastasia A; Daniilidou, Makrina; Tsolaki, Magda (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) has been attributed to chronic bacterial infections. The recognition of human microbiota as a substantial contributor to health and disease is relatively recent and growing. During evolution, mammals live in a symbiotic state with myriads of microorganisms that survive at a diversity of tissue micro-surroundings. Microbes produce a plethora of secretory products [amyloids, lipopolysaccharides, virulence factors rhamnolipids (RLs), toxins, and a great number of neuroactive compounds]. The contribution of infectious microbial components to the pathophysiology of the human central nervous system including AD is considered potentially substantial, but the involvement of the RLs has never been reported. Here, RLs were isolated from serum and identified through various conventional methods including the colorimetric orcinol method, thin-layer chromatography, attenuated total reflection Fourier transform infrared (ATR-FTIR), and dot blot using antibodies against RLs. Dot blot demonstrated elevated RL levels in sera of AD patients compared to controls (p = 0.014). Moreover, ELISA showed similarly elevated RL levels in cerebrospinal fluid of both AD (0.188 versus 0.080) (p = 0.04) and mild cognitive impairment (0.188 versus 0.129) (p = 0.088) patients compared to healthy, and are well-correlated with the AD stages severity assessed using the Mini-Mental State Examination. These results provide conclusive evidence for the newly-reported implication of RLs in AD, adding it to the list of bacterial components, opening new avenues for AD investigation. Moreover, they strengthen and vindicate the divergence of research toward the exploration of bacterial involvement in AD generation and progression.